2011
DOI: 10.1123/ijsc.4.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Framing With Family: Examining Online Coaches’ Biographies for Heteronormative and Heterosexist Narratives

Abstract: Sport scholars have connected heteronormativity and heterosexism to the creation of privilege for the dominant group. They also contend that the coverage and framing of female athletes and coaches promote heteronormativity across print, broadcast, and new media. To date, research examining heteronormativity and heterosexism on university-sponsored athletics Web sites is scarce. Using framing theory, online biographies of NCAA intercollegiate head coaches of 12 conferences (N = 1,902) were examined for textual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The existence of homohysteria among women in sport does more than just marginalize lesbian athletes however, it also re/produces heteronormativity, invoking a societal hierarchy that privileges heterosexuality (Calhoun et al, 2011). Sykes (1998) explains that the fear of 6 lesbianization in women's sport facilitates the silencing of homosexuality in sport, permitting heterosexuality to remain unchallenged; and Hargreaves (1994: 194) shows that media portrayal of female athletes reinforces an image of heterosexuality, stating that "sexualized images" are used with supporting statements about femininity and marital status.…”
Section: Orthodox Notions Of Heterosexual Femininity In Sportmentioning
confidence: 99%
“…The existence of homohysteria among women in sport does more than just marginalize lesbian athletes however, it also re/produces heteronormativity, invoking a societal hierarchy that privileges heterosexuality (Calhoun et al, 2011). Sykes (1998) explains that the fear of 6 lesbianization in women's sport facilitates the silencing of homosexuality in sport, permitting heterosexuality to remain unchallenged; and Hargreaves (1994: 194) shows that media portrayal of female athletes reinforces an image of heterosexuality, stating that "sexualized images" are used with supporting statements about femininity and marital status.…”
Section: Orthodox Notions Of Heterosexual Femininity In Sportmentioning
confidence: 99%
“…The same number of coaches, one, listed their marital status as engaged or widowed (see Tables 2 and 3). One is actually less than the number found by Calhoun et al (2011), as they found two coaches listed a same-sex partner.…”
Section: Examination Of Coaching Biographiesmentioning
confidence: 72%
“…Further, as states continue to legalize same-sex marriages and unions, it will be worthwhile to examine if the lack of partners in coaching biographies continues. While the number of coaches listing same-sex partners actually decreased from the previous study of biographies (Calhoun et al, 2011), one may expect the number to increase if homosexuality continues to become more socially acceptable nationwide. In all, the avenues for future research are plentiful.…”
Section: Limitations and Future Researchmentioning
confidence: 82%
See 2 more Smart Citations